KEDUDUKAN MENTERI AD INTERIM DALAM SISTEM PEMERINTAHAN (TELAAH SIYASAH SYAR’IYYAH) - Ariansyah, Ariansyah; Jafar, Usman (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
The position of the minister as an aide to the president sometimes experiences obstacles that require the president to appoint an acting minister or an interim ad minister. This article aims to examine the position of the interim ad minister in the system of government with the siyasah syar’iyyah approach, focusing on the issue of how the authority of the minister ad interim, urgency and opinion of the siyasi towards the position of minister ad interim. This research is qualitative research using a statutory approach and a syar’i approach. The results showed that the authority of the interim ad minister is more administrative and limited to issuing policies that are strategic in nature, and in terms of time and nature, the position of the interim ad minister is only temporary or implementing. The existence of an interim ad minister is important enough to fill the vacancy, so that the process of organizing government does not stagnate. Imam al-Mawardi divided the two ministerial positions, namely vizier tanfidzi and wazir tafwidhi and in terms of function, the vizier tafwidhi can be matched with the interim minister.